PENERAPAN AL IDARAH PADA NOER FIKRI OFFSET PALEMBANG - ASTUTI, MAIDIANA MAIDIANA; GUSTIANA, ICEU SRI (I-Economics, 2016)
Management as a science and technology contributed greatly to the success of a company. As a science and technology, development through the management out of borders of countries in accordance with the local culture. Indonesia is a one country that uses the principles of management in corporate management as well as the largest Muslim country in the world. A muslim is obliged to way apply the teaching of Islam in every joint of his life, including in business activities (management) is executed. Company management includes managing the human resource that can be integrated with the teaching of Islam that originated from the Al Quran and Al Hadist.Islamic based management is a new science. It is therefore a few companies that implement it anyway. The application of Islamic management is only done by companies whose owners are a Muslim and a Muslim requires all employees. One of the companies that implement Islamic based management is Noer Fikri Offset. Noer Fikri Offset is engaged in publisingand printing the Quran requires each worker to follow established rules of the Islamic way. Application of Islamic based management of Noer Fikri Offset include recruitment, selection, employment contracts, performance appraisal, training and development and compensation. Where all aspect related management to tha commands and prohibitions of Allah SWT. A part from the advantages and disadvantages in its application, the Islamic based management brings new colors in the Indonesian economy. Islamic based management is considered more appropriate to the personality and characteristics of the Indonesian nation.Key word: Management, Management Islam, Management based Islam, Syariah, Islam